The Pengaruh Consumption Value dalam meningkatkan purchase intention layanan online food delivery pada Clay Craft Restaurant di Renaissance Bali Uluwatu Resort & Spa: Indonesia - I Putu Satria Wirawan; I Nyoman Sukana Sabudi; Ni Luh Gde Sri Sadjuni (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2021)
Purchase Intention refers to the possibility of consumers to buy the product. One aspect that affects purchase intention is the extent to which consumption value drives it. This study was conducted to determine the effect of consumption value (functional value, social value, conditional value and epistemic value) in increasing purchase intention of online food delivery services during the COVID-19 pandemic at Clay Craft Restaurant in Renaissance Bali Uluwatu Resort & Spa. Data collection techniques used in this study were questionnaires, interviews, documentation studies and observation. Respondents in this study amounted to 100 respondents using purposive sampling. The data analysis technique in this research is multiple linear regression, t test, F test, coefficient of determination and effective contribution test. The results of this study indicate that consumption value (functional value, social value, conditional value and epistemic value) simultaneously has a significant effect on Purchase Intention. Based on the results of the coefficient of determination test, it shows that the variables forming the Consumption Value (Functional Value, Social Value, Conditional Value and Epistemic Value) have a contribution of 61.9% in influencing Purchase Intention, while the remaining 38.1% is influenced by other variables not examined in this study.